Survivors of the Shoah: Interviewee: George Soros Part II (Survivors of the Shoah Visual History Foundation, 2000)
Shoah Foundation interview code: 51330 Duration: 01:52:00 Interview with George Soros continued. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Luca Illy.